Attachment and couple satisfaction as predictors of expressed emotion in women facing breast cancer and their partners in the immediate post‐surgery period. Issue 1 (24th November 2016) - Favez, Nicolas; Cairo Notari, Sarah; Antonini, Tania; Charvoz, Linda
Abstract : Objectives: To investigate expressed emotion (EE) in couples facing breast cancer in the immediate post‐surgery period. EE may be predictive of psychological disturbances that hinder both partners' capacities to cope with the stress of the disease. Severity of the disease, attachment tendencies, and couple satisfaction were tested as predictors of EE. Design: The design was cross‐sectional. Couples ( N  =   61) were interviewed 2 weeks after the women's breast surgery. Methods: Expressed emotion was assessed in women and in partners with the Five‐Minute Speech Sample, with a focus on overt and covert criticisms. Self‐reported EE, attachment tendencies, and couple satisfaction were assessed with questionnaires. Hierarchical regression analyses were performed to test the predictors and possible interactions between them. Results: Both partners expressed overt and covert criticisms; women expressed more overt criticisms than did their partners. Cancer stage was inversely related to the number of overt criticisms in women and to the number of covert criticisms in partners. Regression analyses showed that in women, higher attachment anxiety and lower couple satisfaction were positive predictors of overt criticisms; in partners, a higher cancer stage was a negative predictor of overt and covert criticisms. Conclusions: Practitioners should pay attention to the couple relationship in breast cancer. EE is most likely to appear when the cancer stage is low, showing that even when the medical prognosis is optimal, relational and emotional disturbances may occur. Statement of contribution What is already known on this subject? The couple relationship is of paramount importance in breast cancer. Expressed emotion (EE) is related to negative individual and relational psychological outcomes in psychiatric and somatic diseases. Expressed emotion has not yet been studied in the context of breast cancer. What does this study add? Expressed emotion is present in breast cancer situations, especially when the cancer stage is low. There was more EE in women than in their partners. Cancer stage, attachment tendencies, and couple satisfaction are predictors of EE.